DEVELOPMENT OF EFFECTIVE WEB SECURITY MEASURES FOR THE NETWORK BY CONDUCTING PENETRATION TESTING USING THE OWASP FRAMEWORK - Kozlovska , Mariia; Piskozub , Andrian (Ukrainian Information Security Research Journal, 2024)
With each step in the development of technology, web security is becoming a more relevant component for ensuring the reliability and protection of network systems. The growing number of cyber threats and potential security breaches emphasizes the need to improve the protection of network systems. To help developers and administrators in this process, there is an important tool - the OWASP (Open Web Application Security Project) framework. It provides a wide range of tools, guidelines, and resources for securing web applications. This framework helps developers check web applications for potential vulnerabilities and find ways to fix them. To better understand, you can imagine that the network is a house and web applications are its doors and windows. If these doors and windows are not tightly closed, attackers can easily get in and cause damage. So, to put it in comparison, just as you check if all the doors and windows in your network are secure, OWASP provides a means to check web applications for vulnerabilities that can be exploited by attackers. Therefore, using the OWASP framework is an important step in developing effective web security measures for your network, helping to ensure that your system is reliable and protected from possible cyberattacks and malicious actions.